Relationship between composite dietary antioxidants index and growth indicators in children aged 3–12 years: results from two observational studies - Wen, Rui; Pei, Huanting; Ren, Jingyi; Zhu, Siqi; Qiao, Simeng; Tan, Pui Yee; Gong, Yunyun; Yang, Min; Huo, Junsheng; Ding, Gangqiang; Ma, Yuxia (Frontiers in Nutrition, 2025)
BackgroundThe intake of nutrients with antioxidant properties is closely related to numerous health outcomes. However, the evidence regarding the effects of antioxidant nutrient intake on children's growth indicators is still lacking. This study aimed to investigate the relationship between the Composite Dietary Antioxidant Index (CDAI) and child growth indicators in two cohorts.MethodsThis study utilized data from 1,064 participants in the Children's Cohort Study on Micronutrient Deficits and Malnutrition (CCSMDM) 2023 database and 2,404 participants from the National Health and Nutrition Examination Survey (NHANES) 2003–2020 database for cross-sectional analyses, with participants aged 3–12 years. The association between CDAI and growth indicators was analyzed using multinomial logistics regression. And we also performed subgroup analyses to determine whether there were differences in gender and explored the dose-response relationship by fitting a restricted cubic spline.ResultsAfter adjusting for potential confounders, CDAI was positively associated with children growth indicators (height: CCSMDM: OR =1.21, 1.04~1.43, p = 0.017; NHANES: OR = 1.11, 1.04~1.18, p = 0.001; weight: CCSMDM: OR =1.27, 1.09~1.52, p = 0.004; NHANES: OR = 1.12, 1.05~1.19, p < 0.001). Our study also found that there was a significant correlation between antioxidant nutrients (vitamin A, vitamin E, zinc, and magnesium) and height. And selenium, magnesium, and BMI were in close contact. Subgroup analysis found that CDAI had a higher positive association with height in male children.ConclusionsOur study revealed the benefits of dietary antioxidant nutrients for children growth indicators. These results suggested that a higher level of dietary antioxidant nutrients may help to promote children growth indicators. It is recommended to consume a combination of multiple antioxidants, as their interactions may offer potential benefits. However, further research is needed to explore the underlying mechanisms of the synergistic effects of antioxidants on children's growth and development.